The Effects of Subjectivity on Manager and Auditor Reporting - Lee, Kyungha (Kari); Menon, Rahul (The Accounting Review, 2019)
ABSTRACT This paper develops an economic model of how subjectivity in accounting estimates affects a manager's reporting behavior and auditors' subsequent information aggregation decision. In our model, the auditor receives a potentially manipulated report from the manager and uses an additional, albeit less precise, estimate to verify the report. We show, perhaps surprisingly, that as subjectivity increases, the auditor puts more weight on the manager's report, but the manager manipulates her report less. The overall effect of subjectivity on audit precision and the expected bias in the audited report is nonmonotonic. We further analyze how subjectivity affects the manager's investment behavior and optimal compensation structure. By introducing the notion of subjectivity, our model provides novel insight and empirical implications on managerial reporting behavior, audit quality, and investment efficiency when involving accounting estimates.